Phenotypic plasticity and genetic variation of Prosopis juliflora (Sw.) DC. across diverse rangelands in northeastern Ethiopia - Minyahel Tilahun; Ayana Angassa; Zinabu Bora; Shimelis Mengistu; Jianshuang Wu (Ecological Processes)
Abstract Introduction Prosopis juliflora (Sw.) DC. substantially threatens dry rangelands due to its invasive attributes, exacerbated by climate change, land-use practices, and anthropogenic activities. Despite the urgent need to understand its ecological impacts, comprehensive studies examining the relationship between its functional traits and reproductive fitness across diverse habitats and land-use scenarios are lacking. This study investigated the functional traits and fitness of Prosopis juliflora in the Afar region of Ethiopia, focusing on three land-use types: dry-season grazing lands, wet-season grazing lands, and wildlife reserves. Methods Plant samples were collected from 192 plots to assess their adaptive potential and genetic variation, alongside relevant physiographic and climatic data. This approach aims to elucidate the contributions of these factors to the observed variation and plasticity of Prosopis juliflora across three rangeland types differing in land use intensity. Generalized linear mixed models and co-occurrence networks were employed to analyze the complex interaction. Results Our findings revealed significant variation in fruiting onset and duration, with wet-season grazing lands demonstrating a shorter duration compared to dry-season grazing lands and wildlife reserves. Genetic variation was significant for total seed mass and number, indicating robust adaptability. The relative growth rate was higher in wildlife reserves compared to dry-season grazing lands, highlighting adaptive advantages in nutrient-rich environments. Additionally, climatic and physiographic analysis identified soil type as a critical factor influencing trait performance. Conclusions This study underscores the urgent need for targeted management strategies to mitigate the ecological impacts of Prosopis juliflora, emphasizing the critical role of soil nutrients in reproductive fitness. Our findings offer valuable insights into the dynamics of invasive species in dry ecosystems and inform conservation efforts.